Analisis Cryptocurrency dalam Fiqih Muamalah: Divergensi Pandangan Ulama terhadap Status Hukum dan Keabsahan Transaksi - Zahran Qolbi Salim; Anik Novita; Aprilia Nabila; Muhammad Faiz Razki Perdana; Tyara Fridayanty Nuramalina; Baidhowi Baidhowi (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The development of cryptocurrency as a digital financial instrument has raised legal issues in Islamic commercial law regarding the legal status and validity of transactions. This study aims to analyze the status of cryptocurrency from an Islamic legal perspective and to examine the divergent views of Indonesian scholars regarding the legitimacy of its use. The method employed is normative legal research using a conceptual and comparative approach through the review of fiqh literature, fatwas, and regulations. The results indicate that the Indonesian Ulema Council (MUI) and Muhammadiyah tend to deem cryptocurrency haram because it involves elements of gharar and maysir, and fails to meet the criteria for a valid means of exchange and a legitimate medium of exchange. Conversely, Nahdlatul Ulama views it as a virtual asset that can be legally exchanged as long as it does not cause harm and is subject to regulatory oversight. The analysis also indicates that price volatility, transaction anonymity, and the dominance of speculation reinforce signs of uncertainty in the contract. The study’s conclusion affirms that the validity of cryptocurrency transactions is conditional and depends on transparency, risk mitigation, and harmonization between Sharia principles and state regulations within the modern digital economic system.